"Labor improbus omnia vincit"; Ambroise Paré and sixteenth century child care. Issue 11 (11th November 2003) - Williams, A N
Abstract : Ambroise Paré (1510–1590) is regarded as one of the greatest surgeons who ever lived. In the sixteenth century, through his example and his writings, Paré did more than anybody else to raise the previously poor reputation of surgery "to one of dignity and esteem." 1 He significantly influenced the surgical management of wounds, especially those produced by gunshot. 2 However, he wrote widely on other areas as well. Although Paré's writings on obstetrics 3 and infant feeding 4 have been previously described, there has been little attention given to the other paediatric cases described in his case notes, which this review now addresses.